‘Textbook truths’ and political dilemmas: The image of Ancient Macedonia in 19th century Greek historiography - Sarakinski, Vojislav; Jovanovski, Dalibor (University of Primorska, Koper, Slovenia, 2016)
There are numerous documents that provide various information about the Greek aspirations toward the region of Macedonia. A question that keeps reappearing is when those aspirations began and how large a territory they encompassed. Early statements of representatives of the Greek political and intellectual elite show that during the time the Greek state was in its infancy, Macedonia was not a political priority. Greek opinions on Ancient Macedonia and Macedonian kings replicate this impeccably. We follow the presentation of ancient Macedonians from ‘barbarians’ and ‘enslavers’ in the 1830s, to ‘Hellenes’ and ‘saviours of Hellenism’ in the 1850s, showing that ancient Macedonians, proclaimed to be Greeks by the means of a textbook, became a focal point of Greek historiography for reasons that were closer to Realpolitik than to scholarly and scientific truth.